IDDF2020-ABS-0163 Reduced survival post-endoscopy for upper gastrointestinal bleeding in the COVID-19 era is a secondary effect of the response to the global pandemic. (18th November 2020) - Tavabie, Oliver; Clough, Jennie; Blackwell, Jonathan; Bashyam, Maria; Martin, Harry; Soubieres, Anet; Direkze, Natalie; Graham, David; Groves, Christopher; Preston, Sean; DeMartino, Sabina; Gill, Upkar; et al.
Abstract : Background: The COVID-19 pandemic has placed increased strain on healthcare systems worldwide with enormous reorganisation undertaken to support 'COVID-centric' services. Non-COVID-19 admissions have been shown to have reduced due to public health measures to halt viral transmission. We aimed to understand the impact of the response to the COVID-19 pandemic on the outcomes of upper gastrointestinal bleeds (UGI). Methods: A pan-London retrospective observational multi-centre study comparing outcomes following endoscopy for UGI bleeds from 24th March 2020 to 20th April 2020 to the corresponding dates in 2019. Primary outcome was in-hospital survival at 30 days with secondary outcomes of major re-bleeding within 30 days post-procedure and intervention at time of endoscopy. Results: 224 endoscopies for 203 patients with UGI bleeds were included within this study. 19 patients were diagnosed with COVID-19. There was a 44.4% reduction in the number of procedures performed between 2019 and 2020. Endoscopies performed for UGI bleeds in the COVID-19 era were associated with an adjusted reduced 30-day survival (OR 0.25, 95% CI 0.08–0.67) (figure 1 ). There was no increased risk of major re-bleeding or interventions during this era. Patients with COVID-19 did not have adjusted reduced survival or adjusted increased complication rates. Conclusions: Endoscopy for UGI bleeds in the COVID-19 era is associated with reduced survival. No clear cause has been identified but we suspect this is a secondary effect of the response to the COVID-19 pandemic. Urgent work is required to encourage the public to seek medical help if required and to optimise patient pathways to ensure that the best possible patient care is provided.